2013
DOI: 10.1182/blood-2012-07-441360
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs activate natural killer cells through Toll-like receptor signaling

Abstract: Key Points miRNAs activate NK cells through a TLR–NF-κB signaling pathway and may have therapeutic applications in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 37 publications
1
59
0
1
Order By: Relevance
“…Therefore, we next determined whether TLRs mediated PL-C-induced IFN-γ production by human NK cells. Others and we have found that human NK cells mainly express TLR1, TLR3, and TLR6 (41, 54). We thus started the experiment by antibody blocking of these TLRs.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, we next determined whether TLRs mediated PL-C-induced IFN-γ production by human NK cells. Others and we have found that human NK cells mainly express TLR1, TLR3, and TLR6 (41, 54). We thus started the experiment by antibody blocking of these TLRs.…”
Section: Resultsmentioning
confidence: 76%
“…Human PBMCs and NK cells were freshly isolated from leukopaks (American Red Cross, Columbus, OH) as described previously (41). PBMCs were isolated by Ficoll-Paque Plus (GE Healthcare Bio-Sciences, Pittsburgh, PA) density gradient centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…NF-κB activation and further activate human NK cells directly. For the role of NF-κB in NK cell activation, we propose that the activation of NF-κB signaling would enhance the activation or cytotoxicity of NK cells by promotion of IFN-γ production and perforin or granzyme expression as previously reported [23][24][25]. Moreover, the stimulation of TLR7 and TLR8 signaling can lead to the overall activation and maturation of APCs, such as macrophages and DCs, accompanied by high expression of co-stimulatory molecules and secretion of pro-inflammatory cytokines and type I IFN, and further fully activate effector NK, NKT and T cells to drive more potent immune responses [6].…”
Section: Discussionmentioning
confidence: 84%
“…Whether at the mRNA or protein level, export of such molecules may offer a duel immune evasion strategy in which tumors can increase proliferation while inhibiting immune effector cell cytolytic activity. Finally, recent evidence indicates that circulating specific exogenous miRs, which are also packaged in exosomes, can modify NK cell function (52), and several miRs including miR-21, miR-26a, miR-214, miR-221, and miR-222 have each been shown to negatively regulate PTEN (36,(53)(54)(55)(56). This creates several potential therapeutic targets for enhancing NK cell function that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%